2014
DOI: 10.1109/surv.2013.050813.00137
|View full text |Cite
|
Sign up to set email alerts
|

EXIT Charts for System Design and Analysis

Abstract: Abstract-Near-capacity performance may be achieved with the aid of iterative decoding, where extrinsic soft information is exchanged between the constituent decoders in order to improve the attainable system performance. Extrinsic Information Transfer (EXIT) charts constitute a powerful semi-analytical tool used for analysing and designing iteratively decoded systems. In this tutorial, we commence by providing a rudimentary overview of the iterative decoding principle and the concept of soft information exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 117 publications
(211 reference statements)
1
126
0
Order By: Relevance
“…• In Section III we conceive a new EXIT chart tool [3], relying on soft decision feedback for improving the performance of the system as compared to the hard decision approach, which is achieved at the cost of a modest increase in complexity [6]. The correlation of chips inherent in the m-sequences is exploited for maximizing the Mutual Information (MI).…”
Section: Ieee Transactions On Vehicular Technology 2018mentioning
confidence: 99%
See 3 more Smart Citations
“…• In Section III we conceive a new EXIT chart tool [3], relying on soft decision feedback for improving the performance of the system as compared to the hard decision approach, which is achieved at the cost of a modest increase in complexity [6]. The correlation of chips inherent in the m-sequences is exploited for maximizing the Mutual Information (MI).…”
Section: Ieee Transactions On Vehicular Technology 2018mentioning
confidence: 99%
“…The concept of EXtrinsic Information Transfer (EXIT) charts was introduced by Brink [3,12] as a powerful tool of analysing the convergence behaviour of iteratively decoded systems. Explicitly, the EXIT chart is capable of predicting the specific SNR value, at which a vanishingly low Bit Error Ratio (BER) can be achieved.…”
Section: Exit Chart Analysis For M-sequence Designmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrate that the URC is capable of ensuring a dimming level of 50%. We quantify the benefits of the proposed 4B6B and URC aided VLC schemes by invoking the 17-subcode IRregular Convolutional Code (IRCC) of [6] as the outer decoding component, whose weighting coefficients are optimized using EXtrinsic information Transfer (EXIT) charts [7]. It is demonstrated that the 4B6B and URC aided VLC systems designed offer higher throughput than their BMC aided counterpart.…”
Section: Introductionmentioning
confidence: 99%